PERAN MANAJEMEN LOGISTIK PANGAN TERHADAP STABILITAS HARGA BAHAN POKOK DI INDONESIA - Hertini, Etty Sri; Risdwiyanto, Andriya; Agustina, Wiwit; Munizu, Musran; Malik, Mirza A. (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the role of food logistics management in stabilizing staple food prices in Indonesia. The research method used is a qualitative approach with a descriptive approach. Data were obtained through interviews, observations, and documentation from various parties involved in the food logistics system, such as government agencies, distribution actors, and traders. Data analysis was conducted using an interactive model that includes data reduction, data presentation, and conclusion drawing. Its validity was tested using triangulation techniques. The results indicate that food logistics management plays a significant role in maintaining staple food price stability. Factors such as distribution efficiency, stock management, infrastructure availability, and technology utilization significantly influence market price stability. Inefficiencies in the logistics system lead to supply imbalances, which impact price bottlenecks. Therefore, integrated improvement efforts are needed through infrastructure enhancement, storage system optimization, strengthening coordination between actors, and utilizing digital technology to create an efficient and sustainable food logistics system. This research is expected to contribute to policymaking to maintain staple food price stability and enhance national food security.